A Indústria Petroquímica no Rio Grande do Sul: Trajetória e Contribuições para o Desenvolvimento Regional - Neuri Antonio Zanchet (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2012)
The present study aims at approaching the trajectory of the petrochemical industry in the Southern Brazilian State of Rio Grande do Sul, and emphasizing its degree of contribution to regional development. We used an exploratory research with qualitative and quantitative approaches. The research design is that of "multiple case studies" based on a bibliographical research and a questionnaire applied to the nine enterprises which constitute the South Petrochemical Center. Results indicated that the acquisition of enterprises, such as Copesul, Petroquímica Triunfo and Ipiranga Petroquímica, by the Odebrecht/Mariani consortium represented a milestone in the restructuring of the South Petrochemical Center, integrating the row materials center with the enterprises of the second generation and enabling the Braskem's dominance in the Petrochemical Complex. Regarding the degree of contribution of the enterprises of the South Petrochemical Center to the regional development, we verified that three companies which belong to the Southern Petrochemical Complex show a high degree of contribution to regional development. Socioeconomic aspects associated with the companies, results obtained through cooperation and geographical aspects associated with the region were highly significant in achieving this degree of contribution.